Genre, frames, and writing in research settings - Paltridge, Brian (Pragmatics & beyond, 1997)
This book presents a perspective on genre based on what it is that leads users of a language to recognise a communicative event as an instance of a particular genre. Key notions in this perspective are those of prototype, inheritance, and intertextuality; that is, the extent to which a text is typical of the particular genre, the qualities or properties that are inherited from other instances of the communicative event, and the ways in which a text is influenced by other texts of a similar kind. The texts which form the basis of this discussion are drawn from experimental research reporting in.